The winner's curse - Rutkoski, Marie (Rutkoski, Marie. Winner's trilogy, 2015)
An aristocratic girl who is a member of a warmongering and enslaving empire purchases a slave, an act that sets in motion a rebellion that might overthrow her world as well as her heart.